Metalloproteomics: Unraveling the Metal Binding Proteins of Diverse Metal-Resistant Bacteria - Jamunasri, N.; Iyer, Aswetha; Prabha, M. Lakshmi; Issac, Reya; Murugan, S. (Asian Journal of Chemistry, 2024)
The release of metals into the environment raises serious concerns about their harmful effects on both the wildlife and human health. The biosphere is experiencing with the pervasive presence of heavy metal pollutants such as arsenic (As), cadmium (Cd), mercury (Hg), lead (Pb), chromium (Cr), copper (Cu) and nickel (Ni), which pose significant environmental challenges. While certain metals are essential for regulating fundamental metabolic processes and upholding the overall physiology of microorganisms, excessive exposure to heavy metals can be detrimental to their survival and function. As a result of their remarkable adaptability, microorganisms, particularly bacteria such as Pseudomonas fluorescens, Escherichia coli, Serratia marcescens, Bacillus cereus and Alcaligenes sp., have evolved sophisticated defence mechanisms to combat the stress caused by heavy metals. One such process is the creation of metal-binding proteins (MBPs), which may bind and sequester metals, thus significantly lowering their toxicity in bacteria. Metalloproteomics, a subfield of metallomics, focuses on the discovery and characterization of such metal-binding proteins (MBPs) in metal-resistant bacteria, resulting in the opening of the doors for innovative bioremediation techniques and therapeutic treatments against bacterial diseases. This review explores the intriguing world of MBPs in metal-resistant bacteria and emphasizes their significant role in metal resistance, detoxification and homeostasis. Furthermore, metallochaperones in bacteria have been extensively studied using the metalloproteomic methodologies and techniques utilized in metal-binding proteins. This study also provides useful information on the interactions between these metallochaperones and different MBPs, which advances our understanding of how bacteria respond to exposure to such heavy metals.